Post-thrombotic Syndrome: Preventative and Risk Reduction Strategies Following Deep Vein Thrombosis - Adam M Gwozdz (Radcliffe Medical Media, 2020)
Venous disease is common in the general population, with chronic venous disorders affecting 50–85% of the western population and consuming 2–3% of healthcare funding. It, therefore, represents a significant socioeconomic, physical and psychological burden. Acute deep vein thrombosis, although a well-recognised cause of death through pulmonary embolism, can more commonly lead to post-thrombotic syndrome (PTS). This article summarises the pathophysiology and risk factor profile of PTS, and highlights various strategies that may reduce the risk of PTS, and the endovenous management of iliofemoral deep vein thrombosis. The authors summarise the advances in PTS risk reduction strategies and present the latest evidence for discussion.